Isolation and expression analysis of oil palm suppressor of PPI1 Locus1 (SP1) / Mohd Azrai Loh Mohd Azlan Loh - Mohd Azrai Loh , Mohd Azlan Loh (2022)
SUPPRESSOR OF PPI1 LOCUS1 (SP1) is an important regulator of the translocon at the outer envelope membrane of chloroplasts (TOC) machinery, which is responsible for the import of precursor protein into plastid which effects the plastid biogenesis and functions. Previous studies on Arabidopsis thaliana had reported the upregulation of SP1 would accelerate plastid differentiation during de-etiolation and senescence. SP1 potential effect in improving the plastid differentiation efficiency, makes it an interesting enzyme to study for crop improvement at large. In this study, data mining using NCBI and PalmXplore was able to identify a putative oil palm SP1 homolog namely Elaeis guineensis SP1 (EgSP1) (LOC105060424) that encodes two protein isoforms: X1 and X2 variants. This SP1 homolog contains the C3HC4 (RING-finger) domain that is conserved in SP1 proteins and showed a high sequence identity (73.76% and 73.47% for X1 and X2 variants, respectively) with the Arabidopsis SP1. Moreover, a phylogenetic tree analysis of SP1 proteins from several selected plants showed that EgSP1 clustered together with other monocots species. Next, the coding sequence of EgSP1 was successfully isolated from cDNA derived from leaves RNA. Using specific primers, amplicons with the size of ~1000 bp were obtained, isolated, and cloned into pGEM-T Easy Vectors. After the transformation of pGEM-T Easy Vector harbouring EgSP1 was performed into E. coli cells, seven PCR positive colonies were selected and subjected for plasmid extraction. From sequencing analysis of the plasmids, it was found that only the X1 transcript variants were able to be cloned and none of the plasmids harbour the X2 variants. In addition, quantitative expression analysis (qPCR) of EgSP1 in several vegetative tissues revealed that SP1 transcripts (variant X1) were highly expressed in the leaf tissues, followed by the roots, with the lowest expression in the stem tissues. The findings uncovered in this study may provide the basis for future agricultural applications of the SP1 gene in the development of oil palm genetic improvement.